KOMITE AUDIT, GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN INFORMASI - Utama, Marta (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
Recently, the atmosphere of business and corporation in all over the world especially in Indonesia has been reminded with good corporate governance. Since the storm of corporate mega scandal that led to the downturn of U.S. economy, regulators in many parts of the world have been busy with efforts of finding strong and agile regulation for externally pushed good corporate governance implementation. One of the most important instruments of good corporate governance is audit committee. Many aspects of the regulation are intended to create a good audit committee which functions are as well as the power given by the regulation. With the relationship of audit committee and good corporate governance, this article is intended to give a new perspective of the relationship between those two components and the information disclosures. The presentation will be much like an analysis of regulation instruments that issued by regulatory bodies in Indonesia which are obliged to administrate the financial industry especially that are concerned about audit committee and good corporate governance. This article is expected to give particular important new knowledge about the terms, function and relationship between audit committee, good corporate governance and information disclosures. Thus, we can give our contribution to the process of building good governance in all aspects of our nation.